Dataset on travellers’ acceptance of border control technologies: Insights from METICOS pilot trialsPilot) supported by Zenodo - Sarang Shaikh; Sule Yildirim Yayilgan; Erjon Zoto; Mohamed Abomhara (Data in Brief)
This paper presents a dataset from the METICOS11 https://meticos-project.eu/. project pilot trials related to the acceptance of border control technologies. There was total five pilots held at Tallin Airport, Athens International Airport, Larnaca International Airport, Border Crossing Point Moravita Land Border, and Vienna International Airport. The dataset consists of the data collected using an online questionnaire (survey) to assess travellers’ technology acceptance in terms of their demographics, profiles, and user perceptions along with operational information of border control technologies during their use. The questionnaire items together with their responses are paired samples collected after the travellers use the technology at the METICOS project pilot trials held in five different locations (i.e. four airports, and one land border) during the period of January to August 2023. The ABC-gates were used to assess technology acceptance during all the pilot trials provided by pilot partner of the METICOS. The total size of the dataset is 147 instances and is well-suited for quantitative analysis of assessing technology acceptance indicators for border control technologies. This information can aid policymakers and border control authorities in enhancing the acceptance and the use of these technologies at various border crossing points across Europe.